Comparative electrophysiological responses in anisometropic and strabismic amblyopic children - de Souza Lima LCS (Dove Medical Press, 2017)
Luiz Cláudio Santos de Souza Lima,1 Adalmir Morterá Dantas,2 Guilherme Herzog Neto,1 Eduardo França Damasceno,1 Helena Parente Solari,1 Marcelo Palis Ventura1 1Department of General Surgery, Federal Fluminense University, Niteroi, 2Department of Ophthalmology, Federal University of Rio de Janeiro, Rio de Janeiro, Brazil Purpose: To compare anisometropic hypermetropic amblyopic and strabismic amblyopic responses to pattern electroretinogram (PERG) and pattern visual evocated potential (PVEP). Materials and methods: Fifty-six patients – 18 hypermetropic anisometropic amblyopic children (mean age 9.70±2.5 years), 19 strabismic amblyopic children (mean age 10.30±2.6 years) and 19 normal emetropic subjects (mean age 10.10±2.2 years) – were enrolled in this study. After routine ophthalmic examination, PERG and PVEP were recorded in response to checks reversed at the rate of two reversals/second stimulating macular area. Results: The difference between hypermetropic anisometropic amblyopia and strabismus amblyopia with respect to P100/P50/N95 wave latencies (P=0.055/0.855/0.132) and P100/P50/N95 amplitudes (P=0.980/0.095/0.045) was not statistically significant. However, there was a significant statistical difference between strabismic amblyopia group and controls for P100/P50/N95 latencies (P=0.000/0.006/0.004). Conclusion: Our findings indicated that despite clinical differences between anisometropic amblyopic and strabismic amblyopic patients, no differences were found in the responses of PVEP and PERG. The abnormal components of the PVEP and PERG in amblyopic subjects could reflect a retinal dysfunction in the visual pathway. Keywords: amblyopia, strabismus, pattern electroretinogram, pattern visual evocated potential, anisometropia